FRI0049 Preclinical Characterization of GS-9876, A Novel, Oral SYK Inhibitor That Shows Efficacy in Multiple Established Rat Models of Collagen-Induced Arthritis. (15th July 2016) - Di Paolo, J.; Blomgren, P.; Dolton, M.; Jones, R.; Kropf, J.; Lee, T.; Mitchell, S.; Murray, B.; Suekawa-Pirrone, K.; Wise, S.; Xu, J.; Zhao, Z.; et al.
Abstract : Background: Spleen Tyrosine Kinase (SYK) mediates signaling in a range of hematopoietic cells involved in the initiation and progression of RA including B cells, monocytes, macrophages, dendritic cells, and osteoclasts. There is strong preclinical validation for SYK as a therapeutic target for RA based on cellular data and animal models of disease. We have identified GS-9876 as a potent and selective SYK inhibitor with pharmaceutical properties compatible with once daily oral dosing in human. Objectives: To characterize the cellular activity of GS-9876 on pathologically relevant pathways in RA, and establish target inhibition requireements for efficacy in rat models of arthritis. Methods: The potency and selectivity of GS-9876 were characterized in biochemical and cellular assays. Effects in B cells were measured by inhibition of BCR-mediated protein phosphorylation, CD69 and CD86 expression, and in macrophages by inhibition of immune-complex (IC)-stimulated cytokine release. Cellular selectivity was demonstrated by comparing the inhibition of B cell proliferation versus T cell proliferation. GS-9876 potency in human blood was evaluated by inhibition of phosphorylated SYK (pSYK), CD63 expression on basophils, and CD69 expression on B cells. The in vivo efficacy of GS-9876 was tested in rat models of collagen-induced arthritis (CIA). Results: GS-9876 is a potent SYK inhibitor (IC50 =9.5±4.3 nM) and is highly selective against a panel of 456 other kinases. GS-9876 inhibited anti-IgM stimulated phosphorylation of AKT, BLNK, BTK, ERK, MEK, and PKCδ in human B cells with EC50 values of 24–51 nM. Functionally, GS-9876 inhibited anti-IgM mediated CD69 and CD86 expression on B-cells (EC50 =112±10 nM and 164±15 nM, respectively) and anti-IgM /anti-CD40 co-stimulated B cell proliferation (EC50 =108±55 nM). In human macrophages, GS-9876 inhibited IC-stimulated TNFα and IL-1β release (EC50 =121±77 nM and 9±17 nM, respectively). Anti-CD3/anti-CD28 stimulated T cell proliferation was weakly inhibited (EC50 =1291±398 nM), with selectivity >10-fold versus the inhibition of B cell proliferation. In human blood, GS-9876 blocked SYK phosphorylation, CD69 expression on B cells, and CD63 expression in basophils. GS-9876 demonstrated a dose-dependent improvement in clinical score and histopathology parameters with once-daily dosing in short and long term rat CIA models. Significant efficacy could be achieved with GS-9876 doses that produced trough pSYK inhibition of <50%. Conclusions: GS-9876 is a novel SYK inhibitor that potently inhibits multiple cellular events implicated in RA pathogenesis and displays excellent in vivo efficacy in rat CIA models after once-daily dosing. GS-9876 has markedly improved selectivity over competitor SYK programs. Our data support the development of GS-9876 in inflammatory diseases, with potential for an improved safety profile. Disclosure of Interest: J. Di Paolo Shareholder of: Gilead Sciences, P. Blomgren Shareholder of: Gilead Sciences, M. Dolton Shareholder of: Gilead Sciences, R. Jones Shareholder of: Gilead Sciences, J. Kropf Shareholder of: Gilead Sciences, T. Lee Shareholder of: Gilead Sciences, S. Mitchell Shareholder of: Gilead Sciences, B. Murray Shareholder of: Gilead Sciences, K. Suekawa-Pirrone Shareholder of: Gilead Sciences, S. Wise Shareholder of: Gilead Sciences, J. Xu Shareholder of: Gilead Sciences, Z. Zhao Shareholder of: Gilead Sciences, K. Currie Shareholder of: Gilead Sciences